Community pharmacists require additional support to develop capacity in delivering alcohol‐related health information to older adults. (20th October 2016) - Dare, Julie; Wilkinson, Celia; Garlepp, Michael; Lo, Johnny; Allsop, Steve
Abstract: Objectives: This qualitative study explored the barriers and enablers influencing Western Australian (WA) community pharmacists' knowledge, confidence, willingness and practice in engaging older clients (>60 years) in alcohol‐related health discussions. Methods: Two focus groups were conducted with a total of 14 community pharmacists who had previously completed a formative quantitative survey ( n = 63), and indicated willingness to participate in a follow‐up focus group. Focus group questions, informed by the survey results, explored participants' perceptions about barriers and enablers to delivering health information and advice about alcohol to older clients (60+ years). Shaw and colleagues' theoretical framework was used to understand barriers and enablers in relation to role legitimacy, role adequacy and role support. Key findings: Participants acknowledged that providing health information about alcohol to older clients is a legitimate part of a community pharmacist's role, and most were confident performing this role in situations perceived as core to their professional practice, such as while dispensing medicines. However, many participants identified limited knowledge, skills and confidence in assisting older clients who may have alcohol issues, beyond advising them on medication and alcohol use. Structural barriers such as time and financial barriers were also identified. Conclusion: Routine professional practice including dispensing medicine and home medicine reviews may provide valuable opportunities to engage older clients in alcohol‐related discussions. However, limited knowledge concerning appropriate strategies to assist older clients reduce their alcohol consumption, coupled with limited skills and confidence among community pharmacists in raising sensitive alcohol‐related issues with clients, suggest the need for specific alcohol‐related training and support.